HARMONISASI PERATURAN DAERAH KABUPATEN BOJONEGORO NOMOR 1 TAHUN 2017 TENTANG PERANGKAT DESA TERHADAP PERATURAN PEMERINTAH NOMOR 43 TAHUN 2014 TENTANG PERATURAN PELAKSANAAN TERHADAP UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - William Benaya; Muhammad Abudan (Fakultas Hukum Universitas Tarumanagara, 2018)
The Regional Government is an extension of the central government to carry out government activities for all regions in Indonesia, and how the division and who heads the regional head is also regulated or mentioned in the Constitution of the Republic of Indonesia, namely the Constitution in Article 18. In carrying out government for the entire The Republic of The United States of Indonesia region, an effective and harmonious regional government is needed between the regional government and the central government. Effective and harmonious referred to in this writing are the accordance of regulations between Regional Government and Central Government. Therefore, in the establishment of a Regional Regulation there is a need for communication, consultation and clarification of the RAPERDA that will be made and legalized between agencies in the Regional Government and the Central Government. That way, it is expected that regional regulations will no longer be antithetic with the higher regulations in accordance with Law Number 12 of 2011 concerning the Establishment of Legislation. Regarding if there is a conflict between the Regional Regulations and higher regulations, the cancellation mechanism can be submitted to the Supreme Court.